Benefits of matching consumers' personality: Creating perceived trustworthiness via actual self-congruence and perceived competence via ideal self-congruence - Adnan Zogaj; Dieter K. Tscheulin; Stephan Olk (Psychology & Marketing, 2020)
Endorsers such as social media influencers who aim to match consumers' personality to strengthen their credibility must consider that actual self-congruence and ideal self-congruence have different effects on the main dimensions of credibility: perceived trustworthiness and perceived competence. In our study, we conceptually argue that actual self-congruence is associated more strongly with a closer psychological distance and, in turn, with trustworthy information, and we empirically show that perceived trustworthiness solely mediates the effect of actual self-congruence on consumer behavior. Subsequently, we conceptually argue that ideal self-congruence is more strongly related to ideal skills and therefore should be more strongly related to perceived competence, and we empirically demonstrate that perceived competence solely mediates the effect of ideal self-congruence on consumer behavior. Our findings explain the mechanism behind the effects of actual and ideal self-congruence and demonstrate important differences in authentic and aspirational marketing strategies with regard to creating the perception of trustworthiness and competence via social media influencers.
Keywords: 650; actual self-congruence; competence; credibility; ideal self-congruence; purchase intentions; similarity; trustworthiness